Factors Affecting Teachers in Implementing the Thematic Curriculum in Primary Schools in Uganda: A Case Study of Butogota Primary School Kanungu District. - Twinomujuni, Dorothy (Kabale University, 2025)
The study aimed to investigate the factors affecting teachers in implementing the thematic curriculum in Butogota Primary School, Kanungu District. It was guided by the following specific objectives: to investigate the reasons behind teachers’s resistance to adopting thematic curriculum, establish the challenges teachers face in implementing thematic curriculum, and assess the possible solutions to the challenges facing teachers in implementing thematic curriculum in Butogota Primary School. A descriptive survey research design was used for the study. A questionnaire and observation checklist were used as the instruments for data collection. The study was carried out in all secondary schools in Butogota Primary School, Kanungu District. A total of 67 respondents were targeted by the study. Purposive sampling techniques and simple random sampling were used for sampling techniques. The data was coded and analyzed using the Statistical Package for Social Sciences (SPSS). The findings showed that on factors affecting teachers in implementing the thematic curriculum, the majority of the respondents 60% mentioned thematic curriculums can feel prescriptive as factors affecting teachers in implementing thematic curriculum, it was also found that the majority of respondents 45% of teachers face challenges in implementing thematic curriculums, which often require a variety of engaging materials and activities and the majority 23% of respondents mentioned advocating for teachers to work together in developing thematic units and sharing resources as possible solutions to the challenges facing teachers in implementing the thematic curriculum. The study's findings shed light on the multifaceted reasons behind teacher resistance to adopting thematic curriculum approaches. The study also concluded that in addressing the challenges, it is imperative to prioritize strategies such as encouraging collaboration among teachers to develop thematic units The findings concluded that encouraging teachers to work together to develop thematic units and share resources, as well as providing adequate training and support for implement ing differentiated instruction within these units, would overcome the challenges faced by teachers in addressing the factors affecting teachers in implementing thematic curriculum thematic curriculum in primary schools. The study recommended reviewing and analyzing existing school data on student achievement trends before and after the implementation of thematic curriculums and developing and implementing a professional development program focused on differentiated instruction within thematic units, building on the finding that this is a prioritized solution among teachers to address the reasons behind teachers’s resistance to adopting thematic curriculum in primary schools in Uganda.